Forskolin-induced organoid swelling is associated with long-term cystic fibrosis disease progression. Issue 2 (18th August 2022) - Muilwijk, Danya; de Poel, Eyleen; van Mourik, Peter; Suen, Sylvia W.F.; Vonk, Annelotte M.; Brunsveld, Jesse E.; Kruisselbrink, Evelien; Oppelaar, Hugo; Hagemeijer, Marne C.; Berkers, Gitte; de Winter-de Groot, Karin M.; Heida-Michel, Sabine; et al.
Rationale: Cystic fibrosis (CF) is a monogenic life-shortening disease associated with highly variable individual disease progression which is difficult to predict. Here we assessed the association of forskolin-induced swelling (FIS) of patient-derived organoids with long-term CF disease progression in multiple organs and compared FIS with the golden standard biomarker sweat chloride concentration (SCC). Methods: We retrieved 9-year longitudinal clinical data from the Dutch CF Registry of 173 people with mutations in the cystic fibrosis transmembrane conductance regulator ( CFTR ) gene. Individual CFTR function was defined by FIS, measured as the relative size increase of intestinal organoids after stimulation with 0.8 µM forskolin, quantified as area under the curve (AUC). We used linear mixed-effect models and multivariable logistic regression to estimate the association of FIS with long-term forced expiratory volume in 1 s % predicted (FEV1 pp) decline and development of pancreatic insufficiency, CF-related liver disease and diabetes. Within these models, FIS was compared with SCC. Results: FIS was strongly associated with longitudinal changes of lung function, with an estimated difference in annual FEV1 pp decline of 0.32% (95% CI 0.11–0.54%; p=0.004) per 1000-point change in AUC. Moreover, increasing FIS levels were associated with lower odds of developing pancreatic insufficiency (adjusted OR 0.18, 95% CI 0.07–0.46; p<0.001), CF-related liver disease (adjusted OR 0.18, 95% CI 0.06–0.54; p=0.002) and diabetes (adjusted OR 0.34, 95% CI 0.12–0.97; p=0.044). These associations were absent for SCC. Conclusion: This study exemplifies the prognostic value of a patient-derived organoid-based biomarker within a clinical setting, which is especially important for people carrying rare CFTR mutations with unclear clinical consequences. Forskolin-induced swelling of patient-derived intestinal organoids is associated with long-term cystic fibrosis disease progression, expressed as FEV1 pp decline and development of pancreatic insufficiency, CF-related liver disease and CF-related diabetes https://bit.ly/3tjjJzU